Volymsrapportering vid drivningsarbete - Gustafsson, Niklas (SLU/School for Forest Management, 2009)
Reporting harvested and forwarded volumes are important for the forest industry as it provides information of the size of the stock and facilitates logistics. Figures from Holmen Skog show low reporting frequency. The purpose of this study is to investigate the reason and find suggestions for improvement. A total of 17 machine operators were interviewed using a questionnaire combined with open questions. The results show that the majority of the machine operators find it simple to use the reporting system, although, some of them reports that it doesn’t always work as supposed to. About 25 percent of the interviewed answered that the reason for low reporting frequency is the lack of timber order number. To solve this specific problem increased routine among production leaders is needed. Other suggestions of actions aiming to increase the reporting frequency are using a production technician for support of the production leaders make it possible for machine operators to report service stops Finally, most of machine operators sees the reporting as a natural part of their job and are positive concerning their relation to Holmen Skog.